Three new species of Incrucipulum (Lachnaceae, Helotiales, Ascomycota) from Japan - Tochihara, Yukito; Hosoya, Tsuyoshi (Phytotaxa, 2019)
Three new species of Incrucipulum were described from Japan: I. foliicola and I. pseudosulphurellum on Myrica gale subsp. tomentosa and I. hakonechloae-macrae on Hakonechloa macra. Disposition to Incrucipulum was justified by molecular phylogenetic analysis based on ITS-5.8S, LSU and RPB2 regions, and monophyly of Incrucipulum was also confirmed. Some apomorphic characters of Incrucipulum were identified. By addition of three new species, the genus Incrucipulum now contains 13 species.